Potential of Carbon Nanodots (CNDs) in Cancer Treatment - Walaa Alibrahem; Nihad Kharrat Helu; Csaba Oláh; József Prokisch (Nanomaterials)
Carbon Nanodots (CNDs) are characterized by their nanoscale size (<10 nm), biocompatibility, stability, fluorescence, and photoluminescence, making them a promising candidate for cancer therapy. The difference in the methods of synthesis of CNDs, whether top-down or bottom-up, affects the formation, visual, and surface characteristics of CNDs, which are crucial for their biomedical and pharmaceutical applications. The urgent need for innovative therapeutic strategies from CNDs is due to the limitations and barriers posed by conventional therapies including drug resistance and cytotoxicity. Nano-loaded chemotherapy treatments are highly effective and can enhance the solubility and targeted delivery of chemotherapeutic agents, generate reactive oxygen species (ROS) to induce cancer cell cytotoxicity, and regulate intracellular signaling pathways. Their ability to be designed for cellular uptake and exact intracellular localization further improves their therapeutic potential. In addition to working on drug delivery, CNDs are highlighted for their dual functionality in imaging and therapy, which allows real-time observing of treatment efficacy. Despite the development of these treatments and the promising results for the future, challenges still exist in cancer treatment.